Project Risk Management Using Bayesian Belief Network - ABDİLATİF, ABDİMALİK SHUEİB (İstanbul Kültür Üniversitesi, 2023)
Project risk management using bayesian belief network One of the main motivations in project management is to increase the probability of success of projects. Organizational policies to optimize investments and risks to minimize the possibility of failure are called risk management. Experts have developed several Project Risk Management (PRM) models to assess project management practices and improve the project outcome. The present study develops a general framework and a method to estimate the impact of risks on project performance. It uses Bayesian networks to formalize project management experts' knowledge and to extract knowledge from a database. A real-life case is used to demonstrate how the method can be applied to reduce the risk of project budget/completion time overrun on a project in the construction industry.
Bayesgil İnanç Ağları İle Projelerde Risk Yönetimi
▪ Yüksek lisans tezi.
Keywords: Bayesian Belief Network; Project Management; Knowledge Modeling